The Mapping of Potential Land Conflicts For The Padang-Pekanbaru Toll Road Based On Land Conflict Habits In West Sumatra - Warmansyah, Frinsis; Syah, Nurhasan; Fatimah, Siti (Journal of Ecohumanism, 2025)
Building infrastructures of public facilities including toll roads requiring community land acquisition has the potential conflicts between the government and land owners. These conflicts include price disagreements over land or landowners insisting on not wanting their land to be released for various reasons. This paper aims to map potential conflicts in land acquisition for the Padang-Pekanbaru toll road carried out by the West Sumatra Provincial Government with land owners whose land is mostly customary land. The locus of this study is limited to West Sumatra Province even though the construction of toll roads reaches Pekanbaru. Several previous studies on land conflicts that occurred the most in West Sumatra were the reason for choosing the location of this study. Secondary data is needed in order to trace land acquisition conflicts that occurred in several periods, especially in Indonesia. Content analysis of the results of previous studies is expected to lead recommendations to the government in anticipating conflicts when land acquisition carried out.